2015
DOI: 10.1016/j.aucc.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Certainty and uncertainty about end of life care nursing practices in New Zealand Intensive Care Units: A mixed methods study

Abstract: Keywords:56 57Death and dying, end of life care, intensive care, intensive care nurse, treatment withdrawal, been undertaken to explore EOL care in the context of New Zealand (NZ) intensive care nursing. 10 11Objective: To investigate NZ intensive care nurses' experiences of, and attitudes towards EOL 12 13 care. 15 16Design: Sequential mixed methods study using cross sectional survey with follow-on focus groups. 18 19Methods: NZ intensive care nurses (N=465) across four large tertiary intensive care units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
14
1
4
Order By: Relevance
“…The use of passive limb exercises, while not usually recognized as a treatment, was also debated by nurses in one study where the decision to withdraw this was informed by whether seeing this take place gave families comfort or distress (Coombs et al . )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of passive limb exercises, while not usually recognized as a treatment, was also debated by nurses in one study where the decision to withdraw this was informed by whether seeing this take place gave families comfort or distress (Coombs et al . )…”
Section: Resultsmentioning
confidence: 99%
“…), concern, rapport (Coombs et al . ), relieving burdens (Epstein ), comfort (Heland ) and expressing emotions (Pattison et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…For the nurses, LTE can involve important ethical conflicts related to the role of carer. 11 , 12 , 36 , 37 These ethical conflicts consisted in the fact that the order of withdrawing life support, on occasions, entails the non-application of care measures that could have been maintaining the patients comfort, such as analgesia, postural mobilizations, and nutrition. 11 , 37 In a study by Coombs et al, 12 over half of the nurses surveyed (55%, n = 111) disagreed that withholding and withdrawing life support treatment were ethically the same thing and 78% (n = 159) of nurses felt that withholding treatment was ethically more acceptable than withdrawing the same.…”
Section: Discussionmentioning
confidence: 99%
“…hygiene measures) which guarantee a degree of comfort and are supportive of ensuring a ''good death'' for patients. 2,10,11 However, despite representing a regular component of ICU work, Coombs et al 12 reported that ICU nurses in New Zealand experienced difficulties and were uncertain about the use of continued nutritional support, continued passive limb exercises, the use of deep sedation and the reduction of inspired oxygen for ventilated patients during final stages of life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this type of decision is well accepted by Western physicians, [22][23][24][25][26][27] but Asian physicians tend to be more accepting of withholding such treatment and less accepting of withdrawing treatment that is already in place. 28 Nurses in Europe 29 and Australia 30 tend to be more accepting of withholding or withdrawing life-sustaining treatment, whereas Turkish 31 and Iranian 32 nurses' attitudes range from negative to neutral regarding the use of life-sustaining treatments.…”
Section: Introductionmentioning
confidence: 99%